Generative Artificial Intelligence as Assistive Technology in Life Science Education: An Analytical Examination of Accessibility, Cognitive Support, and Inclusive Pedagogy - Chakraborty, Souvik; Harikrishnan M (Stallion Journal for Multidisciplinary Associated Research Studies, 2026)
Generative Artificial Intelligence (GAI) has become an important development in the field of higher education giving new opportunities to accessibility, cognitive support, and inclusive learning. Students with varied language, socio-economic, and cognitive backgrounds often face chronic learning challenges in learning life science -a field that has complex concepts, abstract biological operations and high cognitive load. The paper analytically reviews the involvement of the generative AI as an assistive technology in life science education and how it could be used to improve accessibility, aid cognitive processes, and support the inclusive design of instruction. The study is based on the qualitative, non-interventionist, and theory-based approach, relying on peer-reviewed articles (2018 to 2025), international policy resources, and accessibility and AI ethics models in higher education. Patterns associated with accessibility features, cognitive scaffolding mechanisms, pedagogical inclusiveness and ethical constraints are studied with the help of thematic content analysis. Based on the analysis, generative AI can be used as a dynamic system of assistance with multilingual clarifications, generative representations, a customised pacing strategy, and step-by-step conceptual scaffolding in accordance with Universal Design of Learning and Cognitive Load Theory. Even so, the results also point to more severe issues, such as an algorithmic bias, disparity in access, and the threat to the learner's epistemic agency. The paper concludes with the assertions that ethical governance, pedagogical alignment and accessibility-oriented design of generative AI are subject to the educational value and that further mixed-method and empirical classroom research are needed to lend conceptual arguments, credence and support evidence-based practice.